Eskimofischplatz : [193-?] - Hettasch, Paul, 1873-1949. (2001)
Black and white photograph of an Inuit fishing station. Several people can be seen processing fish on the wharf. Black and white photograph of an Inuit fishing station. Several people can be seen processing fish on the wharf.